Analisis perubahan penggunaan lahan pertanian menjadi perumahan di kota Padang Panjang - Monsaputra, Monsaputra (Tunas Agraria, 2023)
Based on data from the Land Office of Padang Panjang City in 2016 and 2010 there was a decrease in the number of paddy fields by 42.5 hectares, while settlements increased by 52.9 hectares. The purpose of this study was to see changes in the use of agricultural land into settlements, the spatial pattern of residential land in the 2010-2019 period and to determine the direction of settlement development. Analysis of land use change was carried out by overlaying land use maps in 2010 and 2019, after which an analysis was carried out by creating a buffer against the road. To find out the spatial pattern of land use change in the 2010-2019 period, the Nearest Neighbor (ANN) analysis was carried out. To determine the direction of settlement development, an analysis of the concentration of settlements was carried out in 2010 and 2019 using the centroid point. The results showed that Pasar Baru Village was the area that experienced the highest percentage of land conversion, which was 46%. The majority of these conversions occur at a low population density of 67% and on a road buffer within 50 meters of 64.47%. The spatial pattern of residential land in the 2010-2019 period in the City of Padang Panjang is clustered. The results of the analysis of the direction of settlement development showed that there was a shift in the direction of the settlement to the southeast as far as 300 meters. Berdasarkan data Kantor Pertanahan Kota Padang Panjang pada tahun 2016 dan 2010 terjadi penurunan jumlah lahan sawah sebanyak 42,5 Ha, sedangkan pemukiman mengalami peningkatan 52,9 Ha. Tujuan penelitian ini adalah untuk melihat perubahan penggunaan lahan pertanian menjadi pemukiman, pola spasial lahan permukiman pada periode 2010-2019 dan untuk mengetahui arah pengembangan pemukiman. Analisis perubahan penggunaan tanah dilakukan dengan overlay peta penggunaan lahan  tahun 2010 dan 2019, setelah itu dilakukan analisis dengan membuat buffer terhadap jalan. Untuk mengetahui pola spasial perubahan penggunaan lahan pada periode 2010-2019 dilakukan dengan Analysis Nearest Neighbor (ANN). Untuk mengetahui arah pengembangan pemukiman dilakukan analisis pemusatan pemukiman pada tahun 2010 dan 2019 menggunakan titik centroid. Hasil penelitian menunjukkan bahwa Kelurahan Pasar Baru adalah wilayah yang mengalami persentase konversi lahan paling tinggi yaitu sebesar 46 %. Konversi tersebut mayoritas terjadi pada kepadatan penduduk yang rendah yaitu sebesar 67 % dan pada buffer jalan berjarak 50 meter sebesar 64,47 %. Pola spasial lahan permukiman pada periode 2010- 2019 di Kota Padang Panjang berkerumun (clustered). Hasil analisis arah pengembangan pemukiman diperoleh hasil terjadi pergeseran arah pemukiman ke arah tenggara sejauh 300 meter.